Photochemical Generation of Benzoazetinone by UV Excitation of Matrix-Isolated Precursors: Isatin or Isatoic Anhydride - Rostkowska, Hanna (J Phys Chem A, 2020)
[Image: see text] Benzoazetinone was photochemically generated by UV irradiation of isatin isolated in low-temperature Ar matrixes. Upon UV (λ = 278 nm) excitation of isatin, monomers of the compound underwent decarbonylation and the remaining part of the molecule adopted the benzoazetinone structure or the structure of its open-ring isomer α-iminoketene. The same products (benzoazetinone and α-iminoketene) were generated by UV (λ = 278 nm) induced decarboxylation of matrix-isolated monomers of isatoic anhydride. Photoproduced α-iminoketene appeared in the low-temperature matrixes as a mixture of syn and anti isomers. Photoproducts generated upon λ = 278 nm irradiation of matrix-isolated isatin were subsequently exposed to λ = 532 nm light. That irradiation resulted in the shift of the α-iminoketene–benzoazetinone population ratio in favor of the latter closed-ring structure. The next irradiation at 305 nm caused the shift of the α-iminoketene–benzoazetinone population ratio in the opposite direction, that is, in favor of the open-ring isomer. Neither benzoazetinone nor its α-iminoketene open-ring isomer was generated upon UV (λ = 278 nm) irradiation of phthalimide isolated in Ar matrixes. Instead, the UV-excited monomers of this compound underwent such phototransformations as oxo → hydroxy phototautomerism or degradation of the five-membered ring with release of HNCO and CO. The efficiency of these photoconversions was low.